VENTURE CAPITAL: AN AMERICAN CONCEPT AND ITS PROBLEMS OF IMPLEMENTATION IN DEVELOPING COUNTRIES - Bintang, Sanusi (UI Scholars Hub, 2015)
Venture capital is an American concept. It is an alternative source for financing small businesses, besides other conventional financing sources, such as banking. Among the characteristics of venture capital are the dual-roles of investors, both as capital owners and management of the businesses. The concept has been successfully implemented in the U.S. which can increase investment and job opportunity. However, there are obstacles in implementation of the concept in developing countries, because, among others, lack of conducive environment for its growth including the weaknesses in economic law and its enforcement, and cultural hindrance. This article discusses the U.S. venture capital concept; it’s successful in the U.S. and its problems of implementation in developing countries, and alternative solutions for better implementation in the future.